Epidemiology of new-onset atrial fibrillation following coronary artery bypass graft surgery. Issue 12 (11th January 2018) - Filardo, Giovanni; Damiano, Ralph J; Ailawadi, Gorav; Thourani, Vinod H; Pollock, Benjamin D; Sass, Danielle M; Phan, Teresa K; Nguyen, Hoa; da Graca, Briget
Abstract : Objectives: Postoperative atrial fibrillation (AF) following coronary artery bypass graft surgery (CABG) is significantly associated with reduced survival, but poor characterisation and inconsistent definitions present barriers to developing effective prophylaxis and management. We sought to address this knowledge gap. Methods: From 2002 to 2010, 11 239 consecutive patients without AF underwent isolated CABG at five sites. Clinical data collected for the Society of Thoracic Surgeons (STS) Database were augmented with details on AF detected via continuous in-hospital ECG/telemetry monitoring to assess new-onset post-CABG AF (adjusted for STS risk of mortality); time to first AF; durations of first and longest AF episodes; total in-hospital time in AF; number of in-hospital AF episodes; operative mortality; stroke; discharge in AF; and length of stay (LOS). Results: Unadjusted incidence of new-onset post-CABG AF was 29.5%. Risk-adjusted incidence was 33.1% and varied little over time (P=0.139). Among 3312 patients with post-CABG AF, adjusted median time to first AF was 52 (IQR: 48–55) hours; mean (SD) duration of first and longest events were 7.2 (5.3, 9.1) and 13.1 (10.4, 15.9) hours, respectively, and adjusted median total time in AF was 22 (IQR: 18–26) hours. Adjusted rates of operative mortality, stroke and discharge in AF did not vary significantly over time (P=0.156, P=0.965 and P=0.347, respectively). LOS varied (P=0.035), but in no discernible pattern. Conclusions: Each year, ~800 000 people undergo CABG worldwide; >264 000 will develop post-CABG AF. Onset is typically 2–3 days post-CABG and episodes last, on average, several hours. Effective prophylaxis and management is urgently needed to reduce associated risks of adverse outcomes.